Tourist perceptions of the implementation of health protocols in the tourism sector in Garut regency/ Endang Komesty Sinaga ... [et al.] - Sinaga, Endang Komesty; Nurwitasari, Ayu; Kurniati, Cucu; Komariah, Nur (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
The application of health protocols is an important thing for tourists and managers of tourism business services in the era of adapting to new habits. This research was conducted with the aim of seeing how tourists' perceptions of the application of health protocols in tourism business services in Garut Regency. The method used in this research is descriptive quantitative. The results showed that tourists have a good perception of the SOP(Standard Operational Procedures) for the Implementation of Health Protocols in Tourism Business Services and have also prepared themselves well to welcome a new life in the pandemic era, the implementation of health protocols carried out by the management of tourism business services has also been carried out well.